2023
DOI: 10.3892/etm.2023.12303
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of extracellular vesicles in the treatment of ovarian diseases (Review)

Yixin Zhang,
Jingyu Zhao,
Linqi Han
et al.

Abstract: The ovary is an essential reproductive organ in the female organism and its development seriously affects the physical and mental health of female patients. Ovarian diseases include ovarian cancer, premature ovarian insufficiency (POI) and polycystic ovary syndrome (PCOS). Women should pay attention to the most effective treatments for this condition because it is one of the most prevalent gynecological illnesses at present. Extracellular vesicles (EVs), which are smaller vesicles that mediate the exchange of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Therefore, the potential of exosomes has renewed our interest in their use as delivery systems for various therapeutics [9][10][11]. Regarding OC, recent reviews revealed that exosomes are involved in remodeling the tumor microenvironment, promoting tumor angiogenesis and metastasis, regulating immune metastasis, and the acquisition of chemotherapy resistance [12,13]. In addition, if patient-derived exosomes can be used as transport carriers, immune reactions during administration may be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the potential of exosomes has renewed our interest in their use as delivery systems for various therapeutics [9][10][11]. Regarding OC, recent reviews revealed that exosomes are involved in remodeling the tumor microenvironment, promoting tumor angiogenesis and metastasis, regulating immune metastasis, and the acquisition of chemotherapy resistance [12,13]. In addition, if patient-derived exosomes can be used as transport carriers, immune reactions during administration may be avoided.…”
Section: Introductionmentioning
confidence: 99%